Prevalence of appropriate colorectal cancer screening and preferences for receiving screening advice among people attending outpatient clinics - Natalie Dodd; Elise Mansfield; Mariko Carey; Christopher Oldmeadow (Elsevier, 2018)
Abstract Objective: To examine among people attending outpatient clinics aged 50-74 at average risk of colorectal cancer (CRC): 1) The proportion who report: a) faecal occult blood test (FOBT) within the past two years; and b) colonoscopy within the past five years, including the reasons for undergoing colonoscopy; 2) characteristics associated with under‐screening; 3) For those who are under‐screened, the proportion who are: a) willing to receive help and the acceptability of different methods of receiving help, and; b) unwilling to receive help and reasons for this. Methods: Cross‐sectional survey of 197 participants attending a major regional hospital in New South Wales, Australia. Multivariable logistic regression was used to determine correlates of under‐screening. Results: A total of 59% reported either FOBT in the past two years or colonoscopy in the past five years. Of those reporting colonoscopy in the past five years, 21% were potentially over‐screened. Males were more likely than females to be under‐screened. Of those under‐screened (41%), fewer than half were willing to receive screening advice. Conclusions and implications for public health: A significant proportion of people attending outpatient clinics are under‐screened for CRC, with some people also over‐screened. There is a need to explore strategies to overcome both under‐ and over‐screening.